El capital humano y su relación con la pobreza monetaria en el departamento de Loreto, período 2016 – 2022 - Mori Leon, Joe Deryk (2025)
In this research, we sought to identify the type of relationship and the intensity of this, between human capital and monetary poverty, in the department of Loreto. For this purpose, a non-experimental design was used, with longitudinal data collection. The level of the study is descriptive correlational and the type of study is basic. To collect the data, the data collection form was applied, which corresponds to the research technique called data analysis. The sample was made up of all the annual data of both variables in a period of 7 years. The results of the study show that human capital in Loreto, on average in the study period, is at a low level (32.13 points out of a total of 100) and monetary poverty is at a high level (reaching an average of 34.56% of its total). population); The estimate between the variables studied is 0.251, measured through the Pearson Coefficient. This result does not allow us to accept the research hypothesis, that is, it is not evident that there is an inverse relationship between human capital and monetary poverty in the entity and period under study.